PENDAMPING BELAJAR ATAU GURU BARU? FENOMENA AKTIFITAS IBU DALAM PROSES BDR SISWA SD MASA PANDEMI COVID 19 - Sukma Erni; Yasnel Yasnel; Elya Roza; Melfa Yola; Salmiah Salmiah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The Home Learning Program (BDR), which must be implemented due to the COVID-19 pandemic, directly increases the workload of mothers as learning companions for children to replace teachers' duties. Apart from the facilities used, the difficulties found were related to the division of working time between household work and child assistance, difficulties with children's learning materials, disciplining children to learn. The impact is that learning assistance only becomes a side activity after completing household chores. The difficulties faced by mothers cannot be separated from the level of education, communication between parents and schools (teachers) and the double burden of mothers in household affairs. Program Belajar Dari Rumah (BDR) yang harus dilaksanakan akibat pendemi covid 19 secara langsung menambah beban kerja ibu sebagai pendamping belajar anak menggantikan tugas guru. Selain fasilitas yang digunakan, kesulitan yang ditemukan terkait dengan pembagian waktu kerja antara kerja rumah tangga dan pendampingan anak, kesulitan materi belajar anak, mendisiplinkan anak untuk belajar. Dampaknya pendampingan belajar hanya menjadi kegiatan sambilan setelah meneyelesaikan pekerjaan rumah tangga. Kesulitan yang dihadapi ibu tidak terlepas dari tingkat Pendidikan, komunikasi orang tua dan sekolah (guru) dan beban ganda ibu dalam urusan rumah tangga.